2004
DOI: 10.1074/jbc.m313314200
|View full text |Cite
|
Sign up to set email alerts
|

An Intestinal Parasitic Protist, Entamoeba histolytica, Possesses a Non-redundant Nitrogen Fixation-like System for Iron-Sulfur Cluster Assembly under Anaerobic Conditions

Abstract: We have characterized the iron-sulfur (Fe-S) cluster formation in an anaerobic amitochondrial protozoan parasite, Entamoeba histolytica, in which Fe-S proteins play an important role in energy metabolism and electron transfer. A genomewide search showed that E. histolytica apparently possesses a simplified and non-redundant NIF (nitrogen fixation)-like system for the Fe-S cluster formation, composed of only a catalytic component, NifS, and a scaffold component, NifU. Amino acid alignment and phylogenetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 54 publications
2
90
0
Order By: Relevance
“…The strongly supported groups have also been recovered in previously published analyses using different methods, including maximum-likelihood, and different support measures including bootstrapping (Horner et al 1999;Rotte et al 2001). examined (Katinka et al 2001;LaGier et al 2003; but only the Trichomonas hydrogenosome (Sutak et al 2004) and Giardia mitosome (Tovar et al 2003) have actually been demonstrated to contain the pathway. Entamoeba is so far unique among eukaryotes in that it has lost the mitochondrial homologues of IscS and IscU (Loftus et al 2005), and instead it possesses genes for the homologous proteins NifS and NifU, acquired through horizontal gene transfer from a bacterium related to Campylobacter (Ali et al 2004;van der Giezen et al 2004). The location of this pathway is central to testing the hypothesis that Fe/S cluster assembly is the common function of all mitochondrial homologues.…”
Section: Conclusion Speculations and Outlookmentioning
confidence: 99%
“…The strongly supported groups have also been recovered in previously published analyses using different methods, including maximum-likelihood, and different support measures including bootstrapping (Horner et al 1999;Rotte et al 2001). examined (Katinka et al 2001;LaGier et al 2003; but only the Trichomonas hydrogenosome (Sutak et al 2004) and Giardia mitosome (Tovar et al 2003) have actually been demonstrated to contain the pathway. Entamoeba is so far unique among eukaryotes in that it has lost the mitochondrial homologues of IscS and IscU (Loftus et al 2005), and instead it possesses genes for the homologous proteins NifS and NifU, acquired through horizontal gene transfer from a bacterium related to Campylobacter (Ali et al 2004;van der Giezen et al 2004). The location of this pathway is central to testing the hypothesis that Fe/S cluster assembly is the common function of all mitochondrial homologues.…”
Section: Conclusion Speculations and Outlookmentioning
confidence: 99%
“…Expression of these recombinant proteins was induced with 1 mM isopropyl-␤-thiogalactoside at 30°C for 5-6 h. The histidine-tagged fusion proteins were purified using a HisTrap kit (Amersham Biosciences, Uppsala, Sweden), according to the manufacturer's instructions, essentially in previously described (Ali et al, 2004a). The HisVps26 and HisVps29 recombinant proteins were further purified using Mono Q anion exchange chromatography as described (Ali et al, 2004b). The recombinant EhRab5 and EhRab7A proteins fused to glutathione S-transferase (GST) at the amino terminus were produced as previously described (Saito-Nakano et al, 2004).…”
Section: Recombinant Protein Productionmentioning
confidence: 99%
“…In conclusion, based on the present and previous findings (16,17), we propose the following scenario for the evolution of FeS cluster assembly in Archamoebae: (i) a common ancestor of Mastigamoeba and Entamoeba that inhabited anaerobic niches gained the NIF machinery from e-proteobacteria through LGT; (ii) the genes encoding the NIF machinery were ancestrally duplicated and the components that acquired MTSs replaced the ISC machinery, as observed in Mastigamoeba; and (iii) in Entamoeba, the mitochondrial NIF machinery may have lost its organellar targeting sequences and replaced the cytosolic NIF version, as suggested by our phylogenetic analysis. However, the low resolution of the Archamoeba tree cannot exclude a more parsimonious scenario, in which the mitochondrial NIF machinery was lost and the cytosolic version was retained.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of Helicobacter NifS/NifU and E. histolytica EhNifS/ EhNifU in Escherichia coli, in which both the isc and suf operons have been deleted, supports the growth of mutated bacteria. However, full complementation of the ISC and SUF systems is observed only under anaerobic conditions (17,28). Thus, it seems plausible that the substitution of the ISC machinery with the oxygen-sensitive NIF machinery that occurred in the Mastigamoeba ancestor would have been possible only in anaerobic niches, where this species exists together with NIF-possessing e-proteobacteria (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation